(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Currently, the global food crisis, hunger, and malnutrition are one of the most important and urgent problems. Hundreds of people around the world are dying of hunger and malnutrition. According to a recent report by the United Nations FAO, the number of malnourished people worldwide has exceeded one billion, accounting for more than 6% of the world’s population. Food supply and demand is not only a Mongolian issue but also depends on the global economy due to Mongolia’s inability to meet its food needs. This paper was described in the current situation and future development in the Mongolia food industry. Moreover, based on the current situation identified future orientation and analyze in Mongolia food sector.